If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 1) = 2(3x + 5) Reorder the terms: 8(1 + x) = 2(3x + 5) (1 * 8 + x * 8) = 2(3x + 5) (8 + 8x) = 2(3x + 5) Reorder the terms: 8 + 8x = 2(5 + 3x) 8 + 8x = (5 * 2 + 3x * 2) 8 + 8x = (10 + 6x) Solving 8 + 8x = 10 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 8 + 8x + -6x = 10 + 6x + -6x Combine like terms: 8x + -6x = 2x 8 + 2x = 10 + 6x + -6x Combine like terms: 6x + -6x = 0 8 + 2x = 10 + 0 8 + 2x = 10 Add '-8' to each side of the equation. 8 + -8 + 2x = 10 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 10 + -8 2x = 10 + -8 Combine like terms: 10 + -8 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| H/5-19=2 | | 11(b-875)=517 | | x^3+3x^2=13x+9 | | 6log(x-3)=11 | | x+(x+1)-(x+2)+(x+3)= | | 0=v^2-10v+24 | | 6(x-4)=-3(x-4) | | A/9=123 | | f=-2+4x-1+-1x | | 6z^2=-19z-10 | | H--184/22=30 | | x^2+y^2+16x+12y=0 | | 22/h--184=30 | | S/3=4 | | 0=v^2+12v+27 | | 9s^2-9s=0 | | 6.7=t/4.9 | | 666=91+23c | | X/4-3x/2=-28.4 | | Q+9=7 | | Y=-5x^2+2x+11 | | 6.7m=t/4.9 | | 24(q+445)=-528 | | 2a-4=5b | | 0=w^2+9w+18 | | 21(h-944)=672 | | (U-8)*7=35 | | h+-16=-13 | | 3(y-13)=6y+24 | | r/4.4=2.8 | | 125-3n=83 | | r^2+r=72 |